Pre-service Teachers’ Language Sensitivity Experiences and Endeavors During Internship Program: Insights for Character and Social Education - Pecson, Ryan; Lugtu, Normita (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: What teachers say in class affects learners' behaviours and understanding. As a harbinger of equitable and transformative education, teachers are mandated to promote sensitivity and inclusivity, making it imperative to conduct studies contextualizing preparatory practices to equip future teachers (pre-service teachers) in fostering inclusive education and social inclusion as part of their internship program. Methodology: The study examines the challenges experienced, strategic measures applied, and instructional resources utilized by pre-service teachers in promoting language sensitivity practices among public secondary schools during their student teaching program through the lens of descriptive qualitative (exploratory study) research. Fifteen (15) pre-service teachers acting as team leaders in their respective schools in the City of Balanga and Bataan, Philippines, handling Grades 7 to 10 students, are purposively selected as key informants for the interview. Upon validation of the research instrument, data gathering commenced, assuring compliance with stringent research protocols (i.e., anonymity, consent, and data confidentiality). Thematic analysis, proposed by Braun and Clarke (2006), is employed for the data analysis. Main Findings: The findings reveal that teaching language sensitivity faces key challenges, including a lack of awareness, peer influence, and the normalization of insensitive language. Such challenges may implicate character education initiatives, specifically in catapulting the roles of student-teachers as agents of social value formation. However, strategies to address such challenges are evident, such as vocabulary building, creating safe learning environments, and experiential learning. Instructional resources range from visual aids and reflective writing to multimedia resources and interactive activities. Novelty/Originality of this study: The study posits novelty in its approach in contextualizing language sensitivity endeavors through the lens of pre-service teachers to intensify technical assistance during their internship program